PENGARUH TERPAAN INFORMASI APLIKASI LUNPIA DAN CITRA DESTINASI TERHADAP MINAT BERKUNJUNG KE KOTA SEMARANG - Putri Susiandi, Alya; Setyabudi, Djoko; Naryoso, Agus (Interaksi Online, 2024)
Semarang City, as an important center of trade and tourism, utilizes destination image and information technology to develop its tourism sector. The "Lunpia" application serves as the main information center for tourism in Semarang City, offering features such as transportation access, tourist attractions, local cuisine, and audio guides, making it easier for tourists to explore the city. In addition to digital marketing communication, destination image that promotes natural beauty and satisfying tourism experiences influences tourists' interest to visit. Effective digital marketing communication utilizing the Lunpia Application and building a positive destination image can influence tourists' interest to visit Semarang. However, despite being identified as a popular tourist destination, Semarang faces difficulty in attracting tourists, as evidenced by fluctuations and a decrease in tourist visitation rates from 2018 to 2021. Therefore, this research aims to investigate the influence of the Lunpia Application and destination image on tourists' interest to visit Semarang. This research uses a quantitative method with an explanatory approach. The sampling technique uses Non-probability Sampling with 100 respondents. The theories employed in this research are technological determinism theory and Theory of Reasoned Action. Hypothesis testing uses simple regression analysis assisted by SPSS. The hypothesis results show a sig. value of information exposure from the Lunpia application to interest in visiting Semarang of 0.103, which means there is no influence of Lunpia application information exposure on interest in visiting Semarang City. Meanwhile, the hypothesis test results show a Sig. value of destination image on interest in visiting Semarang City of 0.001, indicating there is an influence of destination image on interest in visiting Semarang City.